1986
DOI: 10.1111/j.1440-1827.1986.tb03114.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Pyrogen by Polymorphonuclear Leukocytes During the Course of Casein‐induced Peritonitis in Rabbits

Abstract: Rabbits with casein‐induced peritonitis were febrile only during the early stage (1.5 to 12 hours) of inflammation. At that stage, peritoneal exudate cells (PEC) had preformed endogenous pyrogen (EP), while blood leukocytes and leukocytes obtained at the later stage of the inflammatory process did not. Early PEC consisted of 99% polymorphonuclear leukocytes (PMN). As early PEC and highly purified PMN (almost 100% pure) released almost identical amounts of EP, we concluded that PMN were the EP‐producing cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…The current study focuses on establishing an experimental animal model to study muscle weakness induced by the injection of a simple inflammatory agent, casein. It is known that this agent induces a strong production of local pro-inflammatory cytokines and acute phase proteins without inducing circulating cytokines [27, 28]. The present results show that casein injection induces accumulation of neutrophils and macrophages at the site of injection, demonstrating the induction of innate inflammatory responses in this model.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The current study focuses on establishing an experimental animal model to study muscle weakness induced by the injection of a simple inflammatory agent, casein. It is known that this agent induces a strong production of local pro-inflammatory cytokines and acute phase proteins without inducing circulating cytokines [27, 28]. The present results show that casein injection induces accumulation of neutrophils and macrophages at the site of injection, demonstrating the induction of innate inflammatory responses in this model.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have shown that this inflammatory agent does not cause systemic production of cytokines, but induces high level production of inflammatory cytokines locally [27, 28]. Interestingly, a unique feature observed in the present study is that muscle protein degradation is found in inflamed muscle without overt signs of muscle damage or injury.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…An early study by Kitamura et al showed that ip casein injection in rabbits induced a long-lasting febrile response without eliciting significant amounts of endogenous pyrogens in the blood (Kitamura et al, 1986), although very high levels of endogenous pyrogens were detected in the peritoneal cavity. In the present study, a striking difference between LPS and casein induced effects is illustrated by the results in Table1.…”
Section: Discussionmentioning
confidence: 99%
“…The milk protein casein is known to elicit inflammation and fever in animals and humans, although its mode of action is not clear (Kitamura et al, 1986;Moissidis et al, 2005). The air pouch is a closed space covered by a membrane resembling the synovial membrane of a joint that creates a mechanical barrier that retains the inflammatory stimulus and products of the inflammatory response (Edwards et al, 1981;Sedgwick et al, 1983).…”
Section: Surgerymentioning
confidence: 99%